Pembentukan Karakter Siswa melalui Implementasi Nilai-Nilai Adab dalam Kitab Minhajul Muta'allim di MA Darul Ulum Karangpandan Rejoso Pasuruan - Fitri Safira Aliah; Jakaria Umro; Miftakhul Munir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education has become one of the primary focuses in educational institutions to address various moral and behavioral challenges among students. Islamic educational institutions, particularly pesantren-based madrasahs, play a strategic role in instilling moral values through the study of classical Islamic texts. This study aimed to analyze the implementation of moral values contained in the book Minhajul Muta'allim in shaping students' character at MA Darul Ulum Karangpandan Rejoso Pasuruan. This research employed a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation involving the principal, teachers, and students. The findings indicate that the implementation of moral values was conducted through systematic planning, classroom learning activities, religious habituation programs, teacher role modeling, and continuous evaluation. These practices contributed to the development of students' religious attitudes, discipline, responsibility, respect for teachers, politeness, honesty, and social awareness. Supporting factors included the commitment of all school members, the religious culture of the madrasah, and exemplary teachers. Meanwhile, differences in students' backgrounds, peer influence outside the school environment, and inconsistency in practicing moral values became the main obstacles. Therefore, the implementation of the moral values contained in Minhajul Muta'allim significantly contributes to strengthening students' character formation within the madrasah environment